Handbook of research on climate change impact on health and environmental sustainability - Dinda, Soumyananda; Gale Group (Hershey, PA Information Science Reference, an imprint of IGI Global, 2016)
This text offers an analysis of various aspects of global warming and its consequences, featuring such topics as assessment of and adaption to climate change, water and its socioeconomic impact, the environmental effects of climate change on human health, and the mitigation of climate change on both a local and global level.
section 1. Health -- section 2. Vulnerability -- section 3. Natural disaster -- section 4. Water -- section 5. Fishery -- section 6. Forestry -- section 7. Land and adaptation -- section 8. Agriculture -- section 9. Adaptive capability -- section 10. Industry -- section 11. Trade -- section 12. Policy and innovation.
Includes bibliographical references and index.
Keywords: Climatic changes; Climatic changes -- Health aspects; Human beings -- Effect of climate on; Water-supply -- Forecasting; Crops and climate